2D:4D biomarker reliability and validity in a within-subject pregnancy-childhood-adolescence cohort - Eichler, Anna; Kaufmann, Franziska; Titzmann, Adriana; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Buchholz, Verena Nadine; Kornhuber, Johannes; Lenz, Bernd (Early Human Development, 2023)
Background: A lot of studies use the second-to-fourth digit length ratio (2D:4D) as a biomarker for intrauterine androgen load to predict behavioral and mental health problems. Thus, knowledge of 2D:4D's metric properties, namely reliability and validity, is essential. Method: 2D:4D handscans were available from 149 adolescents (M = 13.32 years, SD = 0.35) and their mothers. For 88 adolescents, there were also primary-school age handscans (M = 7.87 years, SD = 0.68). Prenatal risks for the 1st to 3rd trimesters were recorded during the 3rd trimester of pregnancy (alcohol exposition: meconium biomarker and maternal self-report; nicotine exposition: maternal self-report; maternal depressive symptoms and subjective stress: questionnaires). Results: The 2D:4D ratio was highly stable from childhood to early adolescence. However, both developmental and sex effects were present: The 2D:4D ratio increased with age and was higher in adolescent girls vs. boys. Significant 2D:4D mother-child associations were found for girls. Significant main effects could be found for the prenatal risk factors alcohol (self-report) and nicotine consumption. Conclusion: In line with earlier studies, the 2D:4D biomarker proved to be an inter-individually stable measure with an intra-individual increase from childhood to early adolescence. Sex differences in adolescence and associations with maternal prenatal health behaviour underline the validity of the biomarker. Findings on heritability emphasize the importance of interpreting 2D:4D results in a sex-specific manner.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 2D:4D ratio; Alcohol; Androgen load; Biomarker; Construct validity; Heritability; Nicotine; Pregnancy risk; Prenatal; Retest reliability; Stability; Testosterone exposure

Anxiety Is Associated With DPPIV Alterations in Children With Selective Mutism and Social Anxiety Disorder: A Pilot Study - Golub, Yulia; Stonawski, Valeska; Plank, Anne-Christine; Eichler, Anna; Kratz, Oliver; Waltes, Regina; von Hörsten, Stephan; Roessner, Veit; Freitag, Christine M. (Frontiers in Psychiatry, 2021)
Background: Both selective mutism (SM) and social anxiety disorder (SAD) are severe pediatric anxiety disorders with the common trait of behavioral inhibition (BI). The underlying pathophysiology of these disorders remains poorly understood, however converging evidence suggests that alterations in several peripheral molecular pathways might be involved. In a pilot study, we investigated alterations in plasma molecular markers (dipeptidyl peptidase-4 [DPPIV], interleukin-6 [IL-6], tumor necrosis factor-beta [TNF-beta] and neuropeptide-Y [NPY]) in children with SM, SAD, and healthy controls, as well as the correlation of these markers to symptom severity.
CRIS-Team WoS Importer:2021-07-23

Are perinatal measures associated with adolescent mental health? A retrospective exploration with original data from psychiatric cohorts - Basedow, Lukas A.; Kuitunen-Paul, Sören; Roessner, Veit; Moll, Gunther; Golub, Yulia; Eichler, Anna (BMC Psychiatry, 2022)
Background: Perinatal markers of prenatal development are associated with offspring psychiatric symptoms. However, there is little research investigating the specificity of perinatal markers for the development of specific disorders. This study aimed to explore if perinatal markers are specifically associated with adolescent substance use disorder (SUDs). Methods: Adolescent participants from two study centers, one for SUD patients (n = 196) and one for general psychopathology (n = 307), were recruited for participation. Since the SUD participants presented with a number of comorbid disorders, we performed a 1-on-1 matching procedure, based on age, gender, and specific pattern of comorbid disorders. This procedure resulted in n = 51 participants from each group. From all participants and their mothers we recorded perinatal markers (mode of birth, weeks of completed pregnancy, birth weight, Apgar score after 5 min) as well as intelligence quotient (IQ). The SUD sample additionally filled out the Youth Safe Report (YSR) as well as the PQ-16 and the DUDIT. We aimed to distinguish the two groups (SUD sample vs. general psychiatric sample) based on the perinatal variables via a logistic regression analysis. Additionally, linear regressions were performed for the total group and the subgroups to assess the relationship between perinatal variables and IQ, YSR, DUDIT and PQ-16. Results: The perinatal variables were not able to predict group membership (X2 [4] = 4.77, p =.312, Cox & Snell R² = 0.053). Odds ratios indicated a small increase in probability to belonging to the general psychiatric sample instead of the SUD sample if birth was completed via C-section. After Bonferroni-correction, the linear regression models showed no relation between perinatal markers and IQ (p =.60, R² = 0.068), YSR (p =.09, R² = 0.121), DUDIT (p =.65, R² = 0.020), and PQ-16 (p =.73, R² =0.021). Conclusion: Perinatal markers were not able to distinguish SUD patients from patients with diverse psychopathologies. This pattern contradicts previous findings, perhaps because our chosen markers reflect general processes instead of specific mechanistic explanations. Future studies should take care to investigate specific prenatal markers and associate them with psychopathology on the symptom level.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Addiction; Adolescents; Apgar; Birth; Mental Disorders; Perinatal

Assessment of parental stress using the "Eltern-Belastungs-Screening zur Kindeswohlgefährdung" (EBSK) - association with emotional and behavioral problems in children - Eichler, Anna; Glaubitz, Katharina; Hartmann, Luisa Carla; Spangler, Gottfried (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2014)
Parental stress is increased in clinical contexts (e.g., child psychiatry) and correlates with behavioral and emotional problems of children. In addition, parental stress can result in a biased parental perception of child's behavior and emotions. These interrelations were examined in a normal (N = 320) and a clinical (N = 75) sample. The "Eltern-Belastungs-Screening zur Kindeswohlgefährdung" (EBSK; Deegener, Spangler, Körner & Becker, 2009) was used for the assessment of parental stress. As expected, increased EBSK scores were overrepresented in the clinical sample. In both samples stressed parents reported having children with more behavioral and emotional problems. Children of stressed parents in turn reported significantly less problems than their parents did. The rating of independent third persons, e.g. teachers, was not available and should be added in future research. Restrictions in methodology and conclusions for practice are discussed.
EVALuna2:23886

Association of Maternal Smoking during Pregnancy with Neurophysiological and ADHD-Related Outcomes in School-Aged Children - Jansone, Karina; Eichler, Anna; Fasching, Peter; Kornhuber, Johannes; Kaiser, Anna; Millenet, Sabina; Banaschewski, Tobias; Nees, Frauke; On Behalf Of The Imac-Mind Consortium (International Journal of Environmental Research and Public Health, 2023)
Data of a longitudinal cohort study were analyzed to investigate the association between prenatal tobacco exposure and electroencephalographical (EEG) power spectrum in healthy, school-aged children as well as its relationship with attention deficit hyperactivity disorder (ADHD)-related symptoms. Group comparisons (exposed, non-exposed) were performed to test whether prenatal tobacco exposure was associated with brain activity and ADHD symptoms, with adjustments made for covariates including child's sex, child's age, maternal age, maternal smoking habit before pregnancy, alcohol consumption during pregnancy, gestation age, and maternal psychopathology. Tobacco-exposed children showed higher brain activity in the delta and theta frequency bands. This effect was independent of the considered covariates. However, the effects on hyperactivity were found to significantly depend on maternal age and alcohol consumption during pregnancy, but not on the amount of exposure. In summary, smoking during pregnancy significantly affected the resting-state brain activity in children, independent of socio-demographic factors, indicating potential long-lasting effects on brain development. Its impact on ADHD-related behavior was shown to be influenced by socio-demographic confounding factors, such as maternal alcohol consumption and the age of the mother.
CRIS-Team Scopus Importer:2023-04-07
Keywords: ADHD; EEG; hyperactivity; maternal smoking; pregnancy; resting-state brain activity

Association of perinatal characteristics with biomarkers of stress and inflammation in young adults: An exploratory study - Plank, Anne-Christine; Maschke, Janina; Mestermann, Stefan; Janson-Schmitt, Johanna; Sturmbauer, Sarah; Eichler, Anna; Rohleder, Nicolas (Comprehensive Psychoneuroendocrinology, 2024)
General peri- and postnatal characteristics may serve as markers linking pre- or early postnatal events to later health outcomes, which in turn are associated with altered stress- and immune system activity. Our exploratory study investigated whether A) the common perinatal measures “birth weight” and “birth mode” and B) the postnatal characteristics “breastfeeding” and “vaccination status” are associated with markers of stress systems – the hypothalamic-pituitary-adrenal (HPA) axis and autonomous nervous system (ANS) – and inflammation in healthy young adults (n = 68, females: 70.6 %, mean age: 24.21 years, SD = 4.38) exposed to psychosocial challenge, the ‘Trier Social Stress Test’ (TSST). Salivary cortisol, alpha-amylase (sAA) and plasma interleukin-6 (IL-6) were assessed before, during and after the TSST. Participants provided information on peri- and postnatal characteristics. Linear regressions were performed to determine whether peri-/postnatal variables predict basal and stress-response-related biomarker levels. Controlling for sex and sex hormone use as relevant confounders, we found a significant association between birth weight and cortisol recovery (p = 0.032), with higher birth weight predicting higher cortisol recovery values. There were no other significant associations between predictor and outcome variables. Our results show that, in healthy young adults of mixed gender, normal-ranged birth weight is related to the cortisol response to psychosocial stress, indicating a long-term association of this perinatal marker with HPA axis function. In contrast, birth weight was not associated with markers of the ANS stress response or inflammation in adulthood. Our results further suggest that the measures birth mode, duration of breastfeeding, and vaccination status at 4 months of age do not relate to markers of the inflammatory and stress systems in adulthood.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Alpha-amylase; Birth weight; Cortisol; IL-6; Perinatal markers; Stress response

Association of prenatal alcohol exposure and prenatal maternal depression with offspring low-grade inflammation in early adolescence - Maschke, Janina; Roetner, Jakob; Bösl, Sophia; Plank, Anne-Christine; Rohleder, Nicolas; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; et al. (International Journal of Environmental Research and Public Health, 2021)
(1) This longitudinal study aimed to investigate the link between prenatal alcohol exposure and prenatal maternal depression with the offspring’s low-grade inflammatory status. (2) Prenatal alcohol exposure was determined via maternal self-report during the 3rd trimester of pregnancy (self-report+: n = 29) and the meconium alcohol metabolite Ethyl Glucuronide (EtG), collected at birth (≥30 ng/g: n = 23). The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for prenatal maternal depressive symptoms during the 3rd trimester (≥10: n = 35). Fifteen years later, 122 adolescents (M = 13.32 years; 48.4% female) provided blood samples for the analysis of high sensitivity C-reactive protein (hsCRP; M = 0.91; SD = 1.28). (3) Higher hsCRP levels were found in EtG positive adolescents (p = 0.036, ηp2 = 0.04) and an inverse non-significant dose–response relation with hsCRP (r = −0.35, p = 0.113). For maternal self-reported prenatal alcohol consumption (p = 0.780, ηp2 = 0.00) and prenatal depressive symptoms (p = 0.360, ηp2 = 0.01) no differences for hsCRP levels between the affected and unaffected groups were found. (4) Adolescents with prenatal alcohol exposure are at risk for low-grade systemic inflammation. The EtG biomarker may be more accurate compared to self-reports. The findings suggest that prenatal maternal depression does not evoke low-grade systemic inflammation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Early adolescence; High-sensitivity C-reactive protein (hsCRP); Low-grade systemic inflammation; Maternal self-report; Meconium ethyl glucuronide (EtG); Pregnancy; Prenatal alcohol exposure (PAE); Prenatal depression

Associations of prenatal depressive symptoms with DNA methylation of HPA axis-related genes and diurnal cortisol profiles in primary school-aged children - Stonawski, Valeska; Frey, Stefan; Golub, Yulia; Rohleder, Nicolas; Kriebel, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Heinrich, Hartmut; et al. (Development and Psychopathology, 2018)

Associations of prenatal depressive symptoms with DNA methylation of HPA axis-related genes and diurnal cortisol profiles in primary school-aged children - Stonawski, Valeska; Frey, Stefan; Golub, Yulia; Rohleder, Nicolas; Kriebel, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Heinrich, Hartmut; Moll, Gunther; et al. (Development and Psychopathology, 2019)
Epigenetic DNA modifications in genes related to the hypothalamic-pituitary-adrenal (HPA) axis are discussed as a mechanism underlying the association between prenatal depression and altered child HPA activity. In a longitudinal study, DNA methylation changes related to prenatal depressive symptoms were investigated in 167 children aged 6 to 9 years. At six candidate genes, 126 cytosine-guanine dinucleotides were considered without correcting for multiple testing due to the exploratory nature of the study. Further associations with the basal child HPA activity were examined. Children exposed to prenatal depressive symptoms exhibited lower bedtime cortisol (p = .003, ηp2 = 0.07) and a steeper diurnal slope (p = .023, ηp2 = 0.06). For total cortisol release, prenatal exposure was related to lower cortisol release in boys, and higher release in girls. Furthermore, prenatal depressive symptoms were associated with altered methylation in the glucocorticoid receptor gene (NR3C1), the mineralocorticoid receptor gene (NR3C2), and the serotonin receptor gene (SLC6A4), with some sex-specific effects (p = .012-.040, ηp2 = 0.03-0.04). In boys, prenatal depressive symptoms predicted bedtime cortisol mediated by NR3C2 methylation, indirect effect = -0.07, 95% confidence interval [-0.16, -0.02]. Results indicate relations of prenatal depressive symptoms to both child basal HPA activity and DNA methylation, partially fitting a mediation model, with exposed boys and girls being affected differently.
EVALuna2:36373

Attention, cognitive control and motivation in ADHD: Linking event-related brain potentials and DNA methylation patterns in boys at early school age - Heinrich, Hartmut; Grunitz, Juliane; Stonawski, Valeska; Frey, Silke; Wahl, Simone; Albrecht, Bjoern; Goecke, Tamme W.; Beckmann, Matthias; Kornhuber, Johannes; Fasching, Peter; Moll, Gunther; Eichler, Anna (Scientific Reports, 2017)
In order to better understand the underpinnings of attention-deficit/hyperactivity disorder (ADHD), we targeted the relationship of attentional, cognitive control and motivational processes with DNA methylation patterns of 60 candidate genes in boys at early school age. Participants (6 to 8 years; N = 82) were selected from a German longitudinal cohort (FRANCES). ADHD-related behaviour was assessed via maternal ratings. Performance and event-related potential measures (inter alia Cue-P3 and Nogo-P3), which were recorded in a motivational go/nogo task, indicated diminished attentional orienting, reduced inhibitory response control and a larger motivational effect on performance in ADHD already at this relatively young age. Methylation patterns were analysed in buccal cell DNA with the Illumina HumanMethylation 450K array. For CpG sites at genes of the dopaminergic (COMT, ANKK1) and the neurotrophic (BDNF, NGFR) system, associations with the Nogo-P3 as well as ADHD symptom severity were found suggesting that these systems are involved in response control deficits in ADHD. Methylation effects related to both functional aspects and ADHD behaviour were also observed for DPP10 and TPH2. Epigenetic mechanisms may play a role in ADHD-associated deficits but findings need to be replicated in larger samples and are limited by the fact that only peripheral methylation could be considered.
EVALuna2:33560

Becoming a Teenager after Early Surgical Ventricular Septal Defect (VSD) Repair: Longitudinal Biopsychological Data on Mental Health and Maternal Involvement - Lang, Laura; Gerlach, Jennifer; Plank, Anne-Christine; Purbojo, Ariawan; Cesnjevar, Robert; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Journal of Clinical Medicine, 2022)
Beside somatic strains of congenital heart diseases (CHD), affected children often show developmental impairments in the long term. Ventricular septal defect (VSD) is the most common congenital heart defect and early surgical repair is associated with positive somatic outcomes. However, psychological adjustment is of lifelong relevance. We investigated 24 children with a surgically-corrected isolated VSD and their mothers from primary school (6–9 years) to adolescence (10–14 years) and compared them to controls. Both times, mothers reported child internalizing/externalizing problems, mothers and children rated child quality of life, and children performed neurodevelopmental tests. Adolescents also rated internalizing/externalizing problems themselves, and their hair cortisol levels were analyzed. Maternal anxiety and proactive parenting behavior were considered as moderators. Results revealed no group differences in child neurodevelopment (language, cognition), externalizing problems, and cortisol levels at any time. In reports from mothers, internalizing problems (depression, anxiety) were elevated in children with a VSD at both times—when mothers reported anxiety symptoms themselves. In adolescent reports, VSD patients’ quality of life was increased and internalizing problems were decreased—proactive parenting behavior went along with decreased symptoms in VSD-affected adolescents and with increased symptoms in controls. The findings pronounce the crucial role of parenting behavior and the influence of maternal anxieties on child mental health after surgical VSD repair and might highlight the need for parent-centered interventions.
CRIS-Team Scopus Importer:2022-12-23
Keywords: adolescence; child development; congenital heart disease; cortisol; longitudinal study; mental health; psychological adjustment; quality of life; stress; ventricular septal defect

Benefits of cohort studies for child and adolescent health: Insights into substance use, the risk to mental health and potential transference possibilities in care provision Nutzen von Kohortenstudien zur Kinder- und Jugendgesundheit: Erkenntnisse über den Substanzkonsum, sein Risiko für die psychische Gesundheit und potenzielle Übertragungsmöglichkeiten in die Versorgung - Nees, Frauke; Eichler, Anna; Banaschewski, Tobias (Monatsschrift Kinderheilkunde, 2024)
Background: Longitudinal cohort studies are critical for understanding the development and course of mental disorders as well as their risk and protective factors, especially with respect to the substance use of parents and children, which can influence the development of psychological abnormalities. Objective: This article explains the significance of cohort studies in the context of parental (prenatal) and personal alcohol and cannabis use during childhood and adolescence as well as the impacts on mental and neurocognitive development into adulthood. Material and methods: A literature search was carried out in MEDLINE to select relevant studies. Results: Prenatal and early alcohol and cannabis use show predictive and long-term effects on mental health and neurocognitive development into early adulthood. Although many cohort studies exist, the evidence is limited and heterogeneous; however, the studies help to understand the influence of factors and to assess the specificity of the long-term consequences of substance use. Conclusion: Cohort studies offer unique insights into the development of health problems and their predictors. By utilizing existing datasets and conducting further investigations, insights can be maximized and integrated into prevention and intervention strategies through a coordinated and holistic response from various actors. This requires a joint commitment at the individual, familial, community and societal levels.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Alcoholic beverages; Cannabis; Mental health; Neurocognitive development; Pregnancy

Child neurodevelopment and mental health after surgical ventricular septal defect repair: risk and protective factors - Eichler, Anna; Kohler-Jonas, Nicola; Stonawski, Valeska; Purbojo, Ariawan; Moll, Gunther; Heinrich, Hartmut; Cesnjevar, Robert; Kratz, Oliver (Developmental Medicine and Child Neurology, 2019)
Aim This case-control study examined the long-term consequences of surgical correction for ventricular septal defect (VSD; the most common congenital heart defect) in infancy. It assessed children who had undergone VSD surgery and the factors related to maternal conditions, surgery, and hospital stay. Method Thirty-nine children (23 females, 16 males; age range 6y 1mo-9y 7mo [mean 7y 4mo, SD 1y]) with repaired isolated, non-syndromic, non-genetic VSD were compared with 39 typically developing children (22 females, 17 males; age range 6y-9y 2mo [mean 7y 3mo, SD 10mo]). The children completed behavioural tests of neurodevelopment and a quality of life (QoL) questionnaire. Mothers rated children's emotional/behavioural symptoms and QoL. Measures of maternal parenting behaviour and psychopathology were treated as moderators. Results Affected children showed reduced language skills (p=0.002) unless mothers reported high parenting behaviour subscale scores (p=0.04). Children's anxiety symptoms were elevated when mothers had anxiety symptoms (p=0.01). Longer hospital stay was associated with lower intelligence (p=0.003) and psychomotor scores (p=0.006). Longer scars predicted elevated child anxiety (p=0.008), and age at surgery and QoL were inversely related (p=0.01). Interpretation Impairments could be mitigated if VSD repair was performed early in life with a relatively small scar and uncomplicated hospital stay. This outcome depends on maternal parenting behaviour and anxiety symptoms. What this paper adds
CRIS-Team WoS Importer:2019-02-21

Comparing self-report and parental report of psychopathologies in adolescents with substance use disorders - Kuitunen-Paul, Sören; Eichler, Anna; Wiedmann, Melina; Basedow, Lukas A.; Roessner, Veit; Golub, Yulia (European Child & Adolescent Psychiatry, 2021)
Both internalizing and externalizing psychopathologies interfere with the treatment of substance use disorders (SUD) in adolescents. Self-reports of psychopathologies are likely biased and may be validated with parental reports. We compared N = 70 standardized self-reports of adolescents entering outpatient SUD treatment (13.2–18.6 years old, 43% female) to parental reports on the same psychopathologies, and explored biases due to gender, age, SUD diagnoses and SUD severity. Bivariate bootstrapped Pearson correlation coefficients revealed several small to moderate correlations between both reporting sources (r = 0.29–0.49, all pcorrected ≤ 0.039). A repeated measures MANOVA revealed moderately stronger parental reports of adolescent psychopathologies compared to adolescent self-reports for most externalizing problems (dissocial and aggressive behaviors, p ≤ 0.016, η2part = 0.09–0.12) and social/attention problems (p ≤ 0.012, η2part = 0.10), but no differences for most internalizing problems (p ≥ 0.073, η2part = 0.02–0.05). Differences were not associated with other patient or parental characteristics including age, gender, number of co-occurring diagnoses or presence/absence of a certain SUD (all puncorrected ≥ 0.088). We concluded that treatment-seeking German adolescents with SUD present with a multitude of extensive psychopathologies. The relevant deviation between self- and parental reports indicate that the combination of both reports might help to counteract dissimulation and other reporting biases. The generalizability of results to inpatients, psychiatry patients in general, or adolescents without SUD, as well as the validity of self- and parental reports in comparison to clinical judgements remain unknown.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Addiction; Behavioral problems; Emotional problems; Inter-rater agreement; Questionnaire; Substance use disorder

Comparison of C-Reactive Protein in Dried Blood Spots and Saliva of Healthy Adolescents - Plank, Anne-Christine; Maschke, Janina; Rohleder, Nicolas; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Eichler, Anna; Moll, Gunther; Kratz, Oliver (Frontiers in Immunology, 2021)
Background/AimDetermining C-reactive protein (CRP) by non-invasive methods is of great interest for research addressing inflammation in young people. However, direct comparisons of such methods applied in children and adolescents are lacking so far. This study aimed to evaluate the association between CRP measured in dried blood spots (DBS CRP) and in saliva (sCRP), two less invasive alternatives to venipuncture, in 12- to 14-year-old adolescents. To evaluate the validity of both measurements in the context of biobehavioral studies, the potential of DBS CRP and sCRP to discriminate between defined BMI subgroups was assessed. Materials and MethodsCRP levels in DBS and saliva collected from 87 healthy adolescents (M = 13.25 years, SD = 0.30, 51.7% females) were determined using high sensitive CRP ELISA for serum and salivary CRP ELISA, respectively. Characteristics and correlation of both measurements were assessed for the total sample and for three subgroups classified by BMI percentile ranges (A: <= 25; B: 26-74; C: >= 75). ResultsIn the total sample, DBS CRP and sCRP were significantly associated (r = 0.59, p < 0.001). Splitting the sample into BMI-dependent subgroups revealed similarly strong associations of DBS CRP with sCRP for all three groups (A: r = 0.51; B: r = 0.61; C: r = 0.53). However, comparing the mean CRP values per BMI subgroup, one-way ANOVA reported significant differences for DBS CRP, but not for sCRP mean values. ConclusionsThe significant correlation of DBS CRP with sCRP was independent of the investigated BMI range groups, yet BMI-dependent distinction was only provided by DBS CRP mean values. Overall, our results suggest that DBS CRP is likely to reflect systemic inflammation more precisely. Salivary CRP can be alternatively determined in studies with adolescents when conditions require it, given the oral health status is assessed. Considering that DBS CRP and sCRP share only 35% of common variance, further studies should examine their specific validity.
CRIS-Team WoS Importer:2022-01-14

Das Eltern-Belastungs-Inventar (EBI) Einsatz und Nutzen in der Kinder- und Jugendpsychiatrie und –psychotherapie - Irlbauer-Müller, Viktoria; Eichler, Anna; Donhauser, Johanna; Poehlmann, Nina E.; Stemmler, Mark; Moll, G.H.; Kratz, Oliver (Diagnostica, 2017)
Keywords: Elterliche Belastung; psychisch/verhaltensauffällige Kinder/Jugendliche; KJP; Diagnostik; Behandlung

Diagnostic Accuracy of the Drug Use Disorder Identification Test and Its Short Form, the DUDIT-C, in German Adolescent Psychiatric Patients - Basedow, Lukas A.; Kuitunen-Paul, Sören; Eichler, Anna; Roessner, Veit; Golub, Yulia (Frontiers in Psychology, 2021)
Background: A common screening instrument for substance use disorders (SUDs) is the Drug Use Disorders Identification Test (DUDIT) which includes a short form regarding only drug consumption (DUDIT-C). We aim to assess if a German version of the DUDIT, adapted for adolescents, is a suitable screening instrument in a sample of adolescent psychiatric patients. Methods: N = 124 (54 female) German adolescent (M = 15.6 + 1.5 years) psychiatric patients completed the DUDIT and received a diagnostic interview (MINI-KID) assessing DSM-5 SUD criteria. A confirmatory factor analysis (CFA), receiver operating characteristic (ROC) curves, the area under the curve (AUC), and Youden’s Index were calculated. Results: A two-factor model of the DUDIT shows the best model fit (CFI = 0.995, SRMR = 0.055, RMSEA = 0.059, WRMR = 0.603). The DUDIT as well as the DUDIT-C show high diagnostic accuracy, with AUC = 0.95 and AUC = 0.88, respectively. For the DUDIT a cut-off value of 8.5 was optimal (sensitivity = 0.93, specificity = 0.91, J = 0.84), while for the DUDIT-C the optimal cut-off value was at 1.5 (sensitivity = 0.86, specificity = 0.84, J = 0.70). Conclusion: This is the first psychometric evaluation of the DUDIT in German, adolescent psychiatric outpatients, using the DSM-5 diagnostic criteria. The DUDIT as well as the DUDIT-C are well suited for use in this population. Since in our sample only few patients presented with a mild or moderate SUD, our results need to be replicated in a sample of adolescents with mild SUD.
CRIS-Team Scopus Importer:2021-07-02
Keywords: adolescence; cut-off; DUDIT; psychoactive drugs; ROC curve; screening; substance use disorder

Did you drink alcohol during pregnancy? Inaccuracy and discontinuity of women's self-reports: On the way to establish meconium ethyl glucuronide (EtG) as a biomarker for alcohol consumption during pregnancy - Eichler, Anna; Grunitz, Juliane; Grimm, Jennifer; Walz, Lisa; Raabe, Eva; Goecke, Tamme W.; Beckmann, Matthias; Kratz, Oliver; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Kornhuber, Johannes (Alcohol, 2016)
Consuming alcohol during pregnancy is one of the most verified prenatal risk factors for impaired child development. Information about the amount of alcohol consumed prenatally is needed to anticipate negative effects and to offer timely support. Women's self-reports are not reliable, often influenced by social stigmas and retrospective recall bias, causing biomarkers of intrauterine ethanol exposure to become more and more relevant. The present study compares both women's gestational and retrospective self-reports of prenatal alcohol consumption with levels of ethyl glucuronide (EtG) in meconium. Women (n = 180) gave self-reports of prenatal alcohol consumption both during their 3rd trimester (gestational self-report) and when their children were 6-8 years old (retrospective self-report). Child meconium was collected after birth and analyzed for EtG. No individual feedback of children's EtG level was given to the women. All analyses were run separately for two cut-offs: 10 ng/g (limit of detection) and 120 ng/g (established by Goecke et al., 2014). Mothers of children with EtG values above 10 ng/g (n = 42) tended to report prenatal alcohol consumption more frequently. There was no trend or significance for the EtG cut-off of 120 ng/g (n = 26) or for retrospective self-report. When focusing on women who retrospectively reported alcohol consumption during pregnancy, a claim to five or more consumed glasses per month made an EtG over the 10 ng/g and the 120 ng/g cut-off more probable. Women whose children were over the 10 ng/g EtG cut-off were the most inconsistent in their self-report behavior, whereas the consistency in the above 120 ng/g EtG group was higher than in any other group. The next step to establish EtG as a biomarker for intrauterine alcohol exposure is to correlate EtG values in meconium with child developmental impairments.
EVALuna2:23752

Die Aussagekraft des Eltern-Belastungs-Screenings zur Kindeswohlgefährdung" (EBSK) in der Praxis - Eichler, Anna; Glaubitz, Katharina; Hartmann, Luisa Carla; Spangler, Gottfried (Kindesmisshandlung und -vernachlässigung, 2011)

Die Bedeutung mütterlicher präpartaler Depression und Mutter-Kind-Bindung für die Entwicklung der kindlichen Emotionsregulation: Erste Befunde einer Längsschnittstudie - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

Die Erfassung elterlicher Belastung mit dem Eltern-Belastungs-Screening zur Kindeswohlgefährdung (EBSK): Zusammenhänge zu Erlebens- und Verhaltensauffälligkeiten beim Kind - Eichler, Anna; Glaubitz, Katharina; Hartmann, Luisa Carla; Spangler, Gottfried (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2014)

Digit ratio (2D:4D) and behavioral symptoms in primary-school aged boys - Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Beckmann, Matthias; Goecke, Tamme W.; Fasching, Peter; Muschler, Marcel-Rene; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Early Human Development, 2018)
The second-to-forth digit length ratio (2D:4D) is considered to be a biomarker for intrauterine androgen levels. It is associated with adult and child mental health problems, primarily with behavioral symptoms and predominantly in males. Using a cross-sectional design, we examined whether 2D:4D was associated with conduct disorder (CD) symptoms in 138 primary-school aged children (54% boys, Mage = 7.70 years) and considered child sex as a moderating factor. Children's digit lengths were measured from hand scans and mothers rated the behavioral/emotional symptoms of their child. The regression analyses revealed that 2D:4D ratios were associated with behavioral symptoms in boys (β = -0.260, p = 0.026), but not in girls (β = -0.040, p = 0.762). Child emotional symptoms, analyzed as a control, were not significantly correlated with 2D:4D. In conclusion, prenatal brain hyperandrogenization - operationalized by the 2D:4D biomarker - could result in behavioral symptoms in boys at early school age, reflecting one predictor for early onset CD. Our data support the use of 2D:4D as a marker of prenatal androgen exposure.
EVALuna2:36369

Effects of an App-Based Mindfulness Intervention during Pregnancy on the Infant’s Prenatal Androgen Exposure: A Randomized Controlled Pilot Trial - Siegmann, Eva-Maria; Eichler, Anna; Buchholz, Verena Nadine; Gerlach, Jennifer; Pontones, Constanza; Titzmann, Adriana; Arnaud, Nicolas; Consortium, Imac Mind; Mühle, Christiane; Beckmann, Matthias; Fasching, Peter; Kratz, Oliver; et al. (Journal of Clinical Medicine, 2023)
Prenatal androgen exposure modulates the development of the brain, with lasting effects on its function and behavior over the infant’s life span. Environmental factors during pregnancy, in particular maternal stress, have been shown to influence the androgen load of the unborn child. We here addressed the research gap on whether a mindfulness intervention or a pregnancy education administered to pregnant women more affects the androgen exposure of the unborn child (quantified by the proxies of second-to-fourth digit length ratio (2D:4D) and anogenital distance assessed one year after delivery and at delivery, respectively). Moreover, we tested the mindfulness intervention’s effects on maternal perceived stress, anxiety, depressiveness, and mindfulness. Pregnant women (gestation weeks 8–14) were randomized to a 15-week app-based mindfulness-oriented intervention (N = 72) or a pregnancy education intervention (control condition; N = 74). The mindfulness-oriented group did not significantly differ from the pregnancy education group in infants’ 2D:4D or anogenital distance (partial η2 ≤ 0.01) or in maternal stress, anxiety, depressiveness, or mindfulness. However, the descriptive results indicate that across pregnancy, stress and anxiety decreased and mindfulness increased in both groups. Overall, this study did not show that the mindfulness intervention (relative to the pregnancy education) reduced the prenatal androgen exposure of the unborn children or improved the maternal outcomes significantly.
CRIS-Team Scopus Importer:2023-10-20
Keywords: digit ratio; mindfulness; prenatal programming

Effects of prenatal alcohol consumption on cognitive development and ADHD-related behaviour in primary-school age: a multilevel study based on meconium ethyl glucuronide - Eichler, Anna; Hudler, Linda; Grunitz, Juliane; Grimm, Jennifer; Raabe, Eva; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Heinrich, Hartmut (The journal of child psychology and psychiatry, 2018)
BACKGROUND: Alcohol intake during pregnancy is considered to be a risk factor for child development. Child biomarkers of intrauterine alcohol exposure have been rarely studied. We investigated whether a meconium alcohol metabolite (ethyl glucuronide, EtG) was associated with cognitive development, ADHD-related behaviour and neurophysiological markers of attention and executive control of children at primary-school age. METHODS: Mothers provided self-report on prenatal alcohol consumption during their 3rd trimester. Meconium samples were collected at birth. A total of 44 children with a meconium EtG above the detection limit (≥10 ng/g) and 44 nonexposed matched controls were compared. A second threshold (≥154 ng/g) was applied to study the dose effects. When children reached primary-school age, mothers rated ADHD-related behaviour, child cognitive development was measured using an IQ test battery, and event-related potentials were recorded during a cued go/nogo task. RESULTS: Children in both EtG-positive groups allocated fewer attentional resources than controls to the go/nogo task (reduced P3 component in go-trials). Children with a meconium EtG above 154 ng/g were also found to have an IQ that was six points lower than the other groups. Within the EtG ≥ 154 ng/g group, there was a positive correlation between EtG value and ADHD-related behaviour. These significant effects were not observed in relation to the maternal self-report data. CONCLUSIONS: Associations between EtG and cognitive deficits, attentional resource capacity and ADHD-related behaviour could be documented with effects that were partially dose-dependent. In addition to maternal self-reports, this biomarker of intrauterine alcohol exposure may be considered as a predictor of child development.
EVALuna2:33526

Effects of prenatal alcohol exposition on cognitive outcomes in childhood and youth: a longitudinal analysis based on meconium ethyl glucuronide. - Roetner, Jakob; Van Doren, Jessica; Maschke, Janina; Kulke, Louisa; Pontones, Constanza; Fasching, Peter A.; Beckmann, Matthias W.; Lenz, Bernd; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (European archives of psychiatry and clinical neuroscience, 2024)
BACKGROUND: Prenatal alcohol exposure (PAE) has been linked to severe, adverse child outcomes. However, little is known regarding subclinical outcomes of low/moderate PAE and its longitudinal consequences, especially regarding neurophysiological and neurocognitive development. A newborn biomarker of PAE, meconium ethyl glucuronide (EtG), has been shown to predict cognitive impairments in primary-school-aged children. The current study investigated the ongoing effects of subclinical PAE in adolescence. METHODS: A sample of n = 96 mother-child dyads of the FRAMES/FRANCES cohort were classified into PAE/no PAE using EtG with a 10 ng/g cutoff. Mothers were recruited during pregnancy and children were assessed during primary-school age (M = 7.57, SD = 0.65, range: 6.00-9.92 years) and adolescence (M = 13.26, SD = 0.31, range: 12.79-14.20 years) on three levels: clinical (ADHD rating), neuropsychological (IQ score and performance in a go/nogo task), and neurophysiological (analysis of P3 event-related potentials (ERP) during said go/nogo task). Developmental outcomes and courses following PAE were assessed using rmANCOVAs, controlling for relevant confounders (socioeconomic status (SES), birth weight, and maternal psychopathology). RESULTS: Neurophysiological impairments emerged for exposed children in the form of diminished attentional resource recruiting in childhood and adolescence (reduced go-P3 amplitudes) with no differences in performance. Neuropsychological testing showed a reduced IQ score for both time points with dose-dependent effects in childhood. Clinical ADHD symptoms were not significantly affected. CONCLUSION: Subclinical PAE, as determined by meconium EtG, has negative developmental consequences on cognitive function that persist from childhood to adolescence. These findings suggest that there is no safe limit for alcohol consumption during pregnancy and that more thorough screening of alcohol consumption during pregnancy is necessary for early identification and treatment of at-risk children.
EVALuna2:538816

Elterliche Belastung und die Zuverlässigkeit von Elternangaben in der Diagnostik psychisch und verhaltensauffälliger Kinder und Jugendlicher - Irlbauer-Müller, Viktoria; Eichler, Anna; Stemmler, Mark; Moll, Gunther; Kratz, Oliver (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2016)

Epigenetic modifications in children associated with maternal emotional stress during pregnancy - Stonawski, Valeska; Frey, Silke; Golub, Yulia; Moll, Gunther; Heinrich, Hartmut; Eichler, Anna (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2018)
Besides typical physical and hormonal changes during pregnancy, this life period is often associated with an increased emotional and mental stress for women. For the child, the time in utero is regarded as a critical developmental period since adverse stimuli during pregnancy can have lasting consequences for the fetal and postnatal health and development. Thus, prenatal depression, anxiety and stress are considered as risk factors for developmental delay, emotional and behavioral problems. Epigenetic modifications, especially modifications in DNA methylation, are discussed as a possible biological mechanism that could explain the association between prenatal emotional stress and altered developmental and health outcomes of the child. This review summarizes evidence for DNA methylation changes related to prenatal emotional stress from studies with a candidate-gene approach as well as epigenome-wide association studies. Problematic issues are discussed and recommendations for future research are presented.
EVALuna2:36372

Exploring Reference Values for Hair Cortisol: Hair Weight versus Hair Protein - Frisch, Nadine; Eichler, Anna; Plank, Anne-Christine; Golub, Yulia; Moll, Gunther; Kratz, Oliver (Therapeutic Drug Monitoring, 2020)
BACKGROUND: As a marker of cumulative cortisol activity, hair cortisol has received attention in clinical and methodological research. Currently, it is common practice to relate hair cortisol concentration (HCC) to hair weight. The present paper explores hair protein concentration (HPC) as another possible reference value for HCC. METHODS: For n = 18 hair samples cut from the posterior vertex, the HCC, HPC, and hair sample weight were determined, and the cortisol-to-weight and cortisol-to-protein ratios were calculated. Correlations were analyzed between HCC, HPC, and hair sample weight as well as between the cortisol-to-weight and cortisol-to-protein ratios. Hair sample weight and HPC were included as independent variables in a stepwise linear regression model to predict HCC. RESULTS: HCC and HPC did not correlate significantly (r = .393, p = .106); however, the correlation between HCC and hair sample weight was significant (r = .520, p = .027). HPC and hair sample weight (r = .605, p = .008) as well as the cortisol-to-weight and cortisol-to-protein ratios (r = .858, p < .000) showed a high correlation. Hair sample weight was the better predictor of HCC (β = .520, p = .027) than HPC (β = .125, p = .657). CONCLUSIONS: The results indicate that hair sample weight is the more suitable reference value for HCC. Thus, the standard cortisol-to-weight ratio should be used as the preferred expression for cumulative cortisol activity measured in scalp hair. However, calculating the cortisol-to-protein ratio can be considered as an alternative if the hair sample weight is not available.
CRIS-Team Scopus Importer:2020-06-30

Exploring Reference Values for Hair Cortisol: Hair Weight Versus Hair Protein. - Frisch, Nadine; Eichler, Anna; Plank, Anne-Christine; Golub, Yulia; Moll, Gunther; Kratz, Oliver (Therapeutic Drug Monitoring, 2020)
BACKGROUND: As a marker of cumulative cortisol activity, hair cortisol has received attention in clinical and methodological research. Currently, it is a common practice to relate the hair cortisol concentration (HCC) to hair weight. This article explores the hair protein concentration (HPC) as another possible reference value for HCC. METHODS: For n = 18 hair samples cut from the posterior vertex, the HCC, HPC, and hair sample weight were determined, and the cortisol-to-weight and cortisol-to-protein ratios were calculated. Correlations were analyzed between the HCC, HPC, and hair sample weight as well as between the cortisol-to-weight and cortisol-to-protein ratios. Hair sample weight and HPC were included as independent variables in a stepwise linear regression model to predict HCC. RESULTS: The HCC and HPC did not correlate significantly (r = 0.393, P = 0.106); however, the correlation between HCC and hair sample weight was significant (r = 0.520, P = 0.027). The HPC and hair sample weight (r = 0.605, P = 0.008) as well as the cortisol-to-weight and cortisol-to-protein ratios (r = 0.858, P < 0.000) showed a high correlation. The hair sample weight was the better predictor of the HCC (β = 0.520, P = 0.027) than HPC (β = 0.125, P = 0.657). CONCLUSIONS: The results indicate that the hair sample weight is the more suitable reference value for the HCC. Thus, the standard cortisol-to-weight ratio should be used as the preferred expression for the cumulative cortisol activity measured in the scalp hair. However, calculating the cortisol-to-protein ratio can be considered as an alternative if the hair sample weight is not available.
EVALuna2:384364
Keywords: hair cortisol; hair protein; hypothalamic-pituitary-adrenal axis; methodology; stress

Genetic variants in the genes of the sex steroid hormone metabolism and depressive symptoms during and after pregnancy - Schneider, Michael; Pretscher, Jutta; Goecke, Tamme; Häberle, Lothar; Engel, Anne; Kornhuber, Johannes; Eichler, Anna; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aim of this study was to conduct an association analysis of depressive symptoms and polymorphisms in the ESR1, PGR, CYP19A1, and COMT genes in pregnant and postpartum women. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for assessment of maternal and fetal health. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of pregnancy, visit 2 was shortly after birth, and visit 3 was 6–8 months after birth. Germline DNA and depression measurements from 361 pregnant women were available for analysis. Six single nucleotide polymorphisms (SNPs) in the above-mentioned genes were genotyped. After reconstruction of haplotypes for PGR (rs1042838 and rs10895068) and CYP19A1 (rs10046 and rs4646), a multifactorial linear mixed model was applied to the data to describe the association between haplotypes and depression values. The single SNPs for ESR1 (rs488133) and COMT (rs4680) were analyzed separately using linear mixed models analogously. Results: The mean antepartum EPDS measurement was 5.1, the mean postpartal measurement after 48–72 h was 3.5, and the mean value 6–8 months postpartum was 4.2. The SNPs in PGR were reconstructed into three haplotypes. The most common haplotype was GG, with 63.43% of patients carrying two copies and 33.52% carrying one copy. For haplotype GA, the group of carriers of two copies (0.28%) was combined with the carriers of one copy (9.70%). Haplotype reconstruction using CYP19A1 SNPs resulted in three haplotypes. The most common haplotype was TC, with 25.48% of patients carrying two copies and 51.52% one copy. None of the haplotype blocks and neither of the two single SNPs showed any significant associations with EPDS values. Conclusions: The candidate haplotypes analyzed in PGR and CYP19A1 and single SNPs in ESR1 and COMT did not show any association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
CRIS-Team Scopus Importer:2022-06-17
Keywords: COMT; CYP19A1; Depression; EPDS; ESR1; PGR; Single nucleotide polymorphisms

Genetic variants in the genes of the stress hormone signalling pathway and depressive symptoms during and after pregnancy - Schneider, Michael; Engel, Anne; Fasching, Peter; Haeberle, Lothar; Binder, Elisabeth B.; Voigt, Franziska; Grimm, Jennifer; Faschingbauer, Florian; Eichler, Anna; Dammer, Ulf; Rebhan, Dirk; Amann, Manuela; et al. (BioMed Research International, 2014)
The aim of this study was to investigate whether single nucleotide polymorphisms (SNPs) in genes of the stress hormone signaling pathway, specifically FKBP5, NR3C1, and CRHR1, are associated with depressive symptoms during and after pregnancy.The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health including the assessment of depressiveness. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of the pregnancy, visit 2 was shortly after birth, and visit 3 was 6-8 months after birth. Germline DNA was collected from 361 pregnant women. Nine SNPs in the above mentioned genes were genotyped. After construction of haplotypes for each gene, a multifactorial linear mixed model was performed to analyse the depression values over time.EPDS values were within expected ranges and comparable to previously published studies. Neither did the depression scores differ for comparisons among haplotypes at fixed time points nor did the change over time differ among haplotypes for the examined genes. No haplotype showed significant associations with depressive symptoms severity during pregnancy or the postpartum period.The analysed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show an association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
EVALuna2:17356

Genome-Wide DNA Methylation Patterns in Children Exposed to Nonpharmacologically Treated Prenatal Depressive Symptoms: Results From 2 Independent Cohorts - Stonawski, Valeska; Roetner, Jakob; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna; Heinrich, Hartmut; Frey, Stefan (Epigenetics Insights, 2020)
Background: Maternal depressive symptoms are a common phenomenon during pregnancy and are related to negative outcomes for child development and health. Modifications in child DNA methylation are discussed as an underlying mechanism for the association between prenatal depressive symptoms and alterations in child outcomes. However, formerly reported genome-wide associations have yet to be replicated. Methods: In an epigenome-wide association study (EWAS), alterations of DNA methylation related to maternal prenatal depressive symptoms were investigated in buccal cell samples from 174 children (n = 52 exposed to prenatal depressive symptoms; 6-9 years old) of the German longitudinal study FRAMES-FRANCES. Whole blood samples from the independent, age-comparable ARIES subsample of the ARIES/ALSPAC study (n = 641; n = 159 exposed to prenatal depressive symptoms; 7-8 years old) were examined as a confirmation sample. Depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale. DNA methylation was analyzed with the Infinium Human Methylation 450k BeadChip. Modifications in single CpGs, regions, and biological pathways were investigated. Results were adjusted for age and birth outcomes as well as postnatal and current maternal depressive symptoms. Analyses were performed for the whole sample as well as separated for sex. Results: The EWAS yielded no differentially methylated CpG or region as well as no accordance between samples withstanding correction for multiple testing. In pathway analyses, no overlapping functional domain was found to be enriched for either sample. A comparison of current and former findings suggests some overlapping methylation modifications from infancy to childhood. Results suggest that there might be sex-specific differential methylation, which should be further investigated in additional studies. Conclusions: The current, mainly nonsignificant, results challenge the assumption of consistent modifications of DNA methylation in children exposed to prenatal depressive symptoms. Despite the relatively small sample size used in this study, this lack of significant results may reflect diverse issues of environmental epigenetic studies, which need to be addressed in future research.
CRIS-Team Scopus Importer:2020-06-26
Keywords: ALSPAC; ARIES; DNA methylation; epigenetics; FRANCES; Pregnancy; prenatal depression

Heart Rate as a Correlate for the Emotional Processing of Body Stimuli in Anorexia Nervosa - Horndasch, Stefanie; Sharon, Elisabeth; Eichler, Anna; Graap, Holmer; Moll, Gunther; Kratz, Oliver (Behavioral Sciences, 2023)
In anorexia nervosa, aberrant emotional reactions toward body stimuli have been discussed. We investigated heart rate as a physiological marker when viewing body stimuli and hypothesized altered HR reactions toward those highly significant and emotional stimuli in anorexia nervosa. In total, 37 anorexia nervosa patients and 43 control participants viewed pictures of women of five different weight categories, while their cardiac activity was recorded. R-R intervals following picture onset were determined, and means were calculated for three distinct time periods. The overall change in HR relative to baseline across all picture categories was greater in the patient group than in the control group (significant effect of “group”, p = 0.002, partial η2 = 0.120). A significant decrease in HR 2 to 8 s after picture presentation was found for pictures of women of extreme weight in both participant groups (significant “category ∗ time segment interaction”, p = 0.01, partial η2 = 0.037) and correlated with scores of sociocultural attitudes toward the appearance for the extremely underweight category (r = −0.33, p = 0.005). Therefore, differential HR reactions for anorexia nervosa patients and control participants were found for body stimuli in general. The highest HR decelerations in response to pictures of strongly underweight and overweight women may reflect emotional processes such as anxiety due to social comparison.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adolescents; anorexia nervosa; body stimuli; heart rate

ItemComplex: A Python-based visualization framework for ex-post organization and integration of large language-based data sets - Janson, Karina; Gottfried, Karl; Reis, Olaf; Kornhuber, Johannes; Eichler, Anna; Deuschle, Michael; Banaschewski, Tobias; Nees, Frauke (European Psychiatry, 2025)
Background: Nowadays both researchers and clinicians alike have to deal with increasingly larger datasets, specifically also in the context of mental health data. Sophisticated tools for dataset visualization of information from various item-based instruments, being questionnaire data or data from digital applications or clinical documentations, are still lacking, specifically for an integration at multiple levels and for use in both data organization and appropriate construction for its valid use in subsequent analyses. Methods: Here we introduce ItemComplex, a python-based framework for ex-post visualization of large data sets. The method exploits the comprehensive recognition of instrument alignments and the identification of new content networks and graphs based on item similarities and shared versus differential conceptual bases within and across data and studies. Results: The ItemComplex framework was evaluated using four existing large data set from four different cohort studies and demonstrated successful data visualization across multi-item instruments within and across studies. ItemComplex enables researchers and clinicians to navigate through big data sets reliably, informed and quickly. Moreover, it facilitates the extraction of new insights into construct representations and concept identifications within the data. Conclusions: The ItemComplex app is an efficient tool in the field of big data management and analysis addressing the growing complexity of modern datasets to harness the potential hidden within these extensive collections of information. It is also easily adjustable for individual data sets and user preferences, both in the research and clinical field.
CRIS-Team Scopus Importer:2025-06-13
Keywords: big data; constructs; content networks; data navigation; data structuring; data visualization; items

Korrelate der Depressivität von Müttern von Grundschulkindern - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

Long-term Associations of an Early Corrected Ventricular Septal Defect and Stress Systems of Child and Mother at Primary School Age - Stonawski, Valeska; Vollmer, Laura; Köhler-Jonas, Janna Nicola; Rohleder, Nicolas; Golub, Yulia; Purbojo, Ariawan; Moll, Gunther; Heinrich, Hartmut; Cesnjevar, Robert; Kratz, Oliver; Eichler, Anna (Frontiers in Pediatrics, 2017)
Introduction: Ventricular septal defect (VSD) is the most common congenital heart defect, with larger VSDs typically being corrected with an open-heart surgery during infancy. Long-term consequences of a VSD-corrective surgery on stress systems of child and mother are still unknown. The aim of the present study is to investigate the associations of an early corrected VSD and diurnal cortisol release of child and mother. Methods: 26 children (12 boys) between 6 and 9 years old, who underwent surgery for an isolated VSD within the first 3 years of life, and their mothers participated in the study. Their diurnal cortisol profiles were compared to a sex-, age-, and socioeconomic status-matched healthy control group. Within the VSD group, associations between cortisol and characteristics of surgery and hospitalization were investigated. Child and mother psychopathological symptoms were considered as a possible interfering mechanism of altered cortisol profiles. Results: Diurnal cortisol profiles of children with an early corrected VSD did not differ from those of controls. However, mothers of affected children exhibited higher cortisol levels in the morning (p < 0.001, [Formula: see text]) and a steeper diurnal cortisol slope (p = 0.016, [Formula: see text]) than mothers of healthy children. Conclusion: Results indicate a favorable development of children with an early corrected VSD, in terms of comparable diurnal cortisol profiles with healthy controls, according to a comparable mother-rated psychopathology. Mothers of affected children reveal altered diurnal cortisol levels, without differences in self-rated psychopathology. This divergence should be clarified in future research.
EVALuna2:33491

Long-Term Associations of an Early Corrected Ventricular Septal Defect and Stress Systems of Child and Mother at Primary School-Age - Stonawski, Valeska; Vollmer, Laura; Köhler-Jonas, Janna Nicola; Rohleder, Nicolas; Golub, Yulia; Purbojo, Ariawan; Moll, Gunther; Heinrich, Hartmut; Cesnjevar, Robert; Kratz, Oliver; Eichler, Anna (Frontiers in Pediatrics, 2018)

Long-Term Effects of Child Early Surgical Ventricular Septal Defect Repair on Maternal Stress. - Gerlach, Jennifer; Decker, Elena S.; Plank, Anne-Christine; Mestermann, Stefan; Purbojo, Ariawan; Cesnjevar, Robert; Kratz, Oliver; Eichler, Anna (Children, 2023)
The ventricular septal defect (VSD) represents the most common congenital heart defect (CHD). The diagnosis of and cardiac surgery for their child's VSD are highly stressful experiences for parents; especially mothers, who are at risk of developing long-lasting stress-related symptoms. This study examined long-term alterations in maternal stress including self-reported psychological and biophysiological stress levels in a case-control design. We investigated 24 mothers of children with an isolated, surgically corrected VSD compared to non-affected controls. Maternal self-reports on psychopathology, everyday stress, parenting stress and hair cortisol concentrations (HCC) were measured during children's primary school age (6-9 years, t1) and early adolescence (10-14 years, t2). In maternal self-reports, psychopathology and stress symptoms in the VSD-group and controls were comparable at t1, whereas at t2, mothers in the VSD-group even showed a decrease in psychopathology. Maternal HCC levels in the VSD-group were significantly lower (hypocortisolism) than HCC levels of controls at t1. This effect was no longer observed at t2 reflecting an approximation of HCC levels in the VSD-group to controls' levels. This study highlights the potential for improved stress hormone balance and psychological well-being in mothers following their child's surgical VSD repair. However, the need for parent-centered interventions is discussed, particularly during peri-operative phases and in early child developmental stages.
EVALuna2:561224

Maternal depression and child development: A prospective analysis of consequences, risk and protective factors - Roetner, Jakob; Petry, Janna; Niekamp, Julia; Maschkel, Janina; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2022)
Maternal depression and child development: A prospective analysis of consequences, risk and protective factors Abstract. Objective: Maternal stress, specifically maternal mental health problems, are considered risk factors for child development. The literature suggests that prenatal depressive symptoms as well as depressive symptoms are a widespread phenomenon during the further development of the child and have repeatedly been shown to have adverse effects on child mental health outcomes. The present study examined the longitudinal relationships between maternal depression (prenatal, postnatal, during childhood and adolescence) and child mental health from childhood to adolescence. Possible risk and protective factors were also considered. Method: N = 112 mothers were assessed for depressive symptoms via a questionnaire at four different timepoints (prenatal, T1; postnatal, T2; during childhood, T3; during adolescence, T4). Children's externalizing and internalizing symptoms (50.9 % girls) were assessed by their mothers both during childhood (M = 7.68, SD = 0.76 years) and during adolescence (M = 13.23, SD = 0.27 years). We evaluated the relationships between maternal depressive symptoms and children's externalizing/internalizing symptoms using multiple regression models and analyzed possible risk and protective factors using moderation analysis. Results: Externalizing/Internalizing symptoms were not directly associated with maternal depressive symptoms, while associations between such symptoms and maladaptive behavior were found in adolescents. The socioeconomic status of families showed a different risk profile for prenatal and postnatal depressive symptoms. The IQ of the children proved to be a risk factor for internalizing symptoms. Conclusions: Maternal depressive symptoms at any time during child development - in combination with further risk factors - have an impact on child mental health. The early identification of maternal symptoms followed by interventions to differentiate between prenatal and postnatal depression - especially in the context of socioeconomic status - are highly relevant for child development.
CRIS-Team WoS Importer:2022-04-08
Keywords: Pränatale Depressivität; kindliche Erlebens- und Verhaltensauffälligkeiten; Risiko- und Schutzfaktoren; sozioökonomischer Status; Intelligenzquotient; Prenatal depression; child behavior; risk and protective factors; socioeconomic status; intelligence quotient

Maternal perinatal or current depressive symptoms and parenting behavior in middle childhood - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)

Mindfulness-based Stress Reduction in Pregnancy: an App-Based Programme to Improve the Health of Mothers and Children (MINDFUL/PMI Study) - Lenz, Bernd; Eichler, Anna; Schwenke, Eva; Buchholz, Verena N.; Hartwig, Charlotte; Moll, Gunther; Reich, Karin; Mühle, Christiane; Volz, Bernhard; Titzmann, Adriana; Beckmann, Matthias; Heinrich, Hartmut; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Unfavourable intrauterine environmental factors increase the risk of delivery complications as well as postpartum developmental and behavioural problems in children and adolescents with ongoing effects into older age. Biomarker studies show that maternal stress and the use of alcohol and tobacco during pregnancy are associated with a higher intrauterine testosterone exposure of the child. The antenatal testosterone load, in turn, is a risk factor for lasting adverse health effects which extend into adulthood. A 15-week, mindfulness-oriented, app-based programme for the reduction of stress as well as for the reduction of alcohol and tobacco use in pregnant women is established. In the monocentre, prospective, controlled, and investigator-blinded MINDFUL/PMI (Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention) study, pregnant women carry out the programme. Its effect on antenatal testosterone exposure of the child is examined by assessing the index/ring finger length ratio and other biomarkers in the 1-year-old children. In addition, the programme's effects on self-regulation, the developmental status and the mental health of the children at the age of one year will be investigated. Additional aspects of the course of the pregnancy and delivery represent exploratory study objectives. This longitudinal study project is intended to improve the understanding of the impact of intrauterine environmental factors on early childhood development and health. Maternal stress as well as alcohol and tobacco use during pregnancy are modifiable factors and represent potential preventive targets.
EVALuna2:36366

Parenting stress and the reliability of parental information in the diagnostics of children and adolescents with symptoms of psychiatric and behavioral disorders - Irlbauer-Müller, Viktoria; Eichler, Anna; Stemmler, Mark; Moll, Gunther; Kratz, Oliver (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2017)
Information from parents is regularly used in the diagnostic process of children and adolescents with psychiatric symptoms. But the reliability of this information is debatable, because the parents' own stress can distort their perceptions of the child's symptoms.For each of N = 68 children and adolescents (11-18 years) who were using mental health services for the first time, we evaluated the ratings of a parent and a professional clinician (internalizing, externalizing symptoms, total-problem score). In addition, parenting stress was scored on the Eltern-Belastungs-Inventars (EBI, Tröster, 2011), which measures both child-related stress and parent-related stress as well as total stress.Highly stressed parent ratings differed more from the clinicians' ratings than the ratings of less stressed parents. Additionally, correlations showed that higher parenting stress resulted in larger differences between the parent's and the clinician's assessments. Multiple regressions proved the predictive value of child-caused parenting stress for these differences. These results apply for internalizing symptoms, externalizing symptoms, and total-problem score.Parenting stress should be evaluated systematically in order to carefully assess the value of the information from parents and to determine how it should be included in diagnostic and therapeutical decisions.
EVALuna2:23890

Predicting attention deficit hyperactivity disorder using pregnancy and birth characteristics - Schwenke, Eva; Fasching, Peter; Faschingbauer, Florian; Pretscher, Jutta; Kehl, Sven; Peretz, Roberta; Keller, Andrea; Häberle, Lothar; Eichler, Anna; Irlbauer-Müller, Viktoria; Dammer, Ulf; Beckmann, Matthias; et al. (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: The aim of this study was to evaluate maternal, prenatal, perinatal, and postpartum parameters as risk factors for the later development of an attention deficit hyperactivity disorder (ADHD) in the child. METHODS: Women who had given birth at Erlangen University Hospital between 1996 and 1999 were sent a questionnaire in 2009. The results of the questionnaire were correlated with the prospectively collected data for the births in 1996-1999. RESULTS: A total of 573 mother and child pairs were analyzed. Forty-four of the mothers reported that their child had ADHD (7.7%). No significant associations were found for the following parameters: mother's age; mother's educational level; number of the pregnancy; maternal weight before and at the end of pregnancy; mother's height; alcohol consumption during pregnancy; mode of delivery; gestational week; birthweight; umbilical artery blood values; Apgar score at 5 and 10 min; or breastfeeding. The parameters of smoking in pregnancy and an Apgar score lower than 7 after 1 min were significantly associated with a risk for later development of ADHD. CONCLUSIONS: This analysis of maternal, prenatal, perinatal, and postnatal parameters found that smoking in pregnancy and a low Apgar score 1 min after birth are associated with a significantly greater risk for the development of ADHD. Beyond the question of the causal mechanism involved, this is a relevant finding, since smoking during pregnancy is a preventable risk factor.
EVALuna2:36367

Prenatal alcohol exposure and the facial phenotype in adolescents: A study based on meconium ethyl glucuronide - Maschke, Janina; Roetner, Jakob; Goecke, Tamme; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; Eichler, Anna (Brain Sciences, 2021)
Here, we explore the effects of prenatal alcohol exposure (PAE) in adolescence. We investigated associations between meconium ethyl glucoronide (EtG) and facial malformation. For 29 children (66/63 male/female; M = 13.3, SD = 0.32, 12–14 years), PAE was implemented by newborn meconium EtG and maternal self-reports during the third trimester. Cognitive development was operationalized by standardized scores (WISC V). The EtG cut-off values were set at ≥10 ng/g (n = 32, 24.8% EtG10+) and ≥112 ng/g (n = 20, 15.5% EtG112+). The craniofacial shape was measured using FAS Facial Photographic Analysis Software. EtG10+− and EtG112+-affected children exhibited a shorter palpebral fissure length (p = 0.031/p = 0.055). Lip circularity was smaller in EtG112+-affected children (p = 0.026). Maternal self-reports were not associated (p > 0.164). Lip circularity correlated with fluid reasoning (EtG10+ p = 0.031; EtG112+ p = 0.298) and working memory (EtG10+ p = 0.084; EtG112+ p = 0.144). The present study demonstrates visible effects of the facial phenotype in exposed adolescents. Facial malformation was associated with a child’s cognitive performance in the alcohol-exposed group. The EtG biomarker was a better predictor than maternal self-reports.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Alcohol; Biomarker; Craniofacial shape; Ethyl glucuronide (EtG); Facial malformations; Inner canthal distance; Intrauterine alcohol exposure; Lip circularity; Meconium; Palpebral fissure length

Prenatal Alcohol Exposure Is Associated With Adverse Cognitive Effects and Distinct Whole-Genome DNA Methylation Patterns in Primary School Children - Frey, Silke; Eichler, Anna; Stonawski, Valeska; Kriebel, Jennifer; Wahl, Simone; Gallati, Sabina; Goecke, Tamme W.; Fasching, Peter A.; Beckmann, Matthias W.; Kratz, Oliver; Moll, Gunther; Heinrich, Hartmut; et al. (Frontiers in Behavioral Neuroscience, 2018)
Prenatal alcohol exposure (PAE) is known to elicit a broad range of systemic effects, including neurophysiological alterations that result in adverse behavioral and cognitive outcomes. However, molecular pathways underlying these long-term intrauterine effects remain to be investigated. Here, we tested a hypothesis that PAE may lead to epigenetic alterations to the DNA resulting in attentional and cognitive alterations of the children. We report the results of the study that included 156 primary school children of the Franconian Cognition and Emotion Studies (FRANCES) cohort which were tested for an objective marker of PAE, ethyl glucuronide (EtG) in meconium at birth. Thirty-two newborns were found to be exposed to alcohol with EtG values above 30 ng/g (EtG+). Previously we described PAE being associated with lower IQ and smaller amplitude of the event-related potential component P3 in go trials (Go-P3), which indicates a reduced capacity of attentional resources. Whole-genome methylation analysis of the buccal cell DNA revealed 193 differentially methylated genes in children with positive meconium EtG, that were clustered into groups involved in epigenetic modifications, neurodegeneration, neurodevelopment, axon guidance and neuronal excitability. Furthermore, we detected mediation effects of the methylation changes in DPP10 and SLC16A9 genes on the EtG related cognitive and attention-related deficits. Our results suggest that system-wide epigenetic changes are involved in long-term effects of PAE. In particular, we show an epigenetic mediation of PAE effects on cognition and attention-related processes.
EVALuna2:36368

Prenatal and adult androgen activities in alcohol dependence - Lenz, Bernd; Mühle, Christiane; Braun, B.; Weinland, C.; Bouna-Pyrrou, Polyxeni; Behrens, Juliane; Kubis, S.; Mikolaiczik, Katrin; Muschler, M. -R.; Saigali, Sarah; Sibach, M.; Tanovska, P.; et al. (Acta Psychiatrica Scandinavica, 2017)
OBJECTIVE: Alcohol dependence is more prevalent in men than in women. The evidence for how prenatal and adult androgens influence alcohol dependence is limited. We investigated the effects of prenatal and adult androgen activity on alcohol dependence. Moreover, we studied how the behaviours of pregnant women affect their children's prenatal androgen load. METHOD: We quantified prenatal androgen markers (e.g., second-to-fourth finger length ratio [2D : 4D]) and blood androgens in 200 early-abstinent alcohol-dependent in-patients and 240 controls (2013-2015, including a 12-month follow-up). We also surveyed 134 women during pregnancy (2005-2007) and measured the 2D : 4D of their children (2013-2016). RESULTS: The prenatal androgen loads were higher in the male alcohol-dependent patients compared to the controls (lower 2D : 4D, P = 0.004) and correlated positively with the patients' liver transaminase activities (P < 0.001) and alcohol withdrawal severity (P = 0.019). Higher prenatal androgen loads and increasing androgen levels during withdrawal predicted earlier and more frequent 12-month hospital readmission in alcohol-dependent patients (P < 0.005). Moreover, stress levels (P = 0.002), alcohol (P = 0.010) and tobacco consumption (P = 0.017), and lifetime stressors (P = 0.019) of women during pregnancy related positively to their children's prenatal androgen loads (lower 2D : 4D). CONCLUSION: Androgen activities in alcohol-dependent patients and behaviours of pregnant women represent novel preventive and therapeutic targets of alcohol dependence.
EVALuna2:33408

Prenatal Androgen Influence on Addictive Behaviour in Adolescence Vorgeburtlicher Androgen- einfluss auf süchtiges Verhalten in der Adoleszenz - Lenz, Bernd; Eichler, Anna; Buchholz, Verena Nadine; Fasching, Peter; Kornhuber, Johannes (Sucht, 2021)
Background: Men consume alcohol, tobacco, and illicit drugs more often than women, and they are more prone to pathological gambling and addictive internet gaming. These sex differences are already found during adolescence. The consumption patterns are related to externalizing behavior. In addition to social influences, biological factors play a central role in the development of these differences between men and women. Prenatal exposure to androgens and estrogens shape the brain development with functional and structural effects that persist into adulthood. Intrauterine sex hormone exposure is related to maternal risk factors such as stress and substance use. Aim: In this narrative review, we discuss the potential impact of prenatal androgen exposure in the womb on the development of addictive behaviors and self-regulation in later life. In recent years, this issue has been addressed by animal experiments with direct modulation of prenatal androgenization and clinical association studies based on biomarkers such as the second-to-fourth finger lengths ratio (2D:4D). Results: The available body of literature suggests that reinforced brain androgenization during the intrauterine development increases the risk for addictive behaviors and deficits in self-regulation capacity in later life. Finally, we also discuss prevention strategies during pregnancy targeting this model and refer to the Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention study. This investigation is a subproject of the IMAC-Mind research collaborative project to improve mental health and reduce addiction risk in childhood and adolescence through mindfulness.
CRIS-Team Scopus Importer:2021-12-24
Keywords: addiction; adolescence; dependence; prenatal development; testosterone

Salivary and hair cortisol as biomarkers of emotional and behavioral symptoms in 6–9 year old children - Golub, Yulia; Kuitunen-Paul, Sören; Panaseth, Kerstin; Stonawski, Valeska; Frey, Stefan; Steigleder, Ruth; Grimm, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; et al. (Physiology & behavior, 2019)
The aim of the present work is to investigate the association of salivary and cumulative cortisol levels with emotional and behavioral symptoms in a Franconian Cognition and Emotion Studies (FRANCES) general population cohort of 158 6- to 9 year old children. Salivary cortisol values were measured by one-day diurnal cortisol profile, whereas cumulative cortisol was estimated via one-month hair cortisol concentrations (rHCC). Nearly all significant associations of clinical symptoms with child cortisol indices were age dependent: We report emotional symptoms being associated with lower rHCC in younger children (6.06–7.54 years). In older children (7.55–9.41 years) behavioral problems were further associated with higher rHCC and lower salivary cortisol awakening responses. In summary, child clinical symptoms were stronger associated with markers of hair cortisol compared to salivary cortisol. To picture developmental mechanisms, we suggest longitudinal designs for cortisol measures of stress systems in children and adolescents.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Behavioral symptoms; Emotional symptoms; FRANCES; Hair cortisol; HPA axis; Salivary cortisol

Semantic search helper: A tool based on the use of embeddings in multi-item questionnaires as a harmonization opportunity for merging large datasets - A feasibility study - Gottfried, Karl; Janson, Karina; Holz, Nathalie E.; Reis, Olaf; Kornhuber, Johannes; Eichler, Anna; Banaschewski, Tobias; Nees, Frauke (European Psychiatry, 2025)
Background Recent advances in natural language processing (NLP), particularly in language processing methods, have opened new avenues in semantic data analysis. A promising application of NLP is data harmonization in questionnaire-based cohort studies, where it can be used as an additional method, specifically when only different instruments are available for one construct as well as for the evaluation of potentially new construct-constellations. The present article therefore explores embedding models' potential to detect opportunities for semantic harmonization. Methods Using models like SBERT and OpenAI's ADA, we developed a prototype application (Semantic Search Helper) to facilitate the harmonization process of detecting semantically similar items within extensive health-related datasets. The approach's feasibility and applicability were evaluated through a use case analysis involving data from four large cohort studies with heterogeneous data obtained with a different set of instruments for common constructs. Results With the prototype, we effectively identified potential harmonization pairs, which significantly reduced manual evaluation efforts. Expert ratings of semantic similarity candidates showed high agreement with model-generated pairs, confirming the validity of our approach. Conclusions This study demonstrates the potential of embeddings in matching semantic similarity as a promising add-on tool to assist harmonization processes of multiplex data sets and instruments but with similar content, within and across studies.
CRIS-Team Scopus Importer:2025-01-31
Keywords: big data; harmonization; natural language processing; questionnaires; semantic

Sex-specific association between prenatal androgenization (second-to-fourth digit length ratio) and frontal brain volumes in adolescents - Lenz, Bernd; Gerhardt, Sarah; Boroumand-Jazi, Rafat; Eichler, Anna; Buchholz, Verena Nadine; Fasching, Peter; Kornhuber, Johannes; Banaschewski, Tobias; Flor, Herta; Guldner, Stella; Prignitz, Maren; Nees, Frauke (European archives of psychiatry and clinical neuroscience, 2022)
Prenatal androgenization associates sex-dependently with behavior and mental health in adolescence and adulthood, including risk-taking, emotionality, substance use, and depression. However, still little is known on how it affects underlying neural correlates, like frontal brain control regions. Thus, we tested whether prenatal androgen load is sex-dependently related to frontal cortex volumes in a sex-balanced adolescent sample. In a cross-sectional magnetic resonance imaging study, we examined 61 adolescents (28 males, 33 females; aged 14 or 16 years) and analyzed associations of frontal brain region volumes with the second-to-fourth digit length ratio (2D:4D), an established marker for prenatal androgenization, using voxel-based morphometry in a region-of-interest approach. Lower 2D:4D (indicative of higher prenatal androgen load) correlated significantly with smaller volumes of the right anterior cingulate cortex (r-ACC; beta = 0.45) in male adolescents and with larger volumes of the left inferior frontal gyrus orbital part (l-IFGorb; beta = - 0.38) in female adolescents. The regression slopes of 2D:4D on the r-ACC also differed significantly between males and females. The study provides novel evidence that prenatal androgenization may influence the development of the frontal brain in a sex- and frontal brain region-specific manner. These effects might contribute to the well-known sex differences in risk-taking, emotionality, substance use, and depression. Future research is needed to elucidate the role of prenatal androgenization within the biopsychosocial model.
CRIS-Team WoS Importer:2022-12-23

Sleep behavior and problems in children and adolescents of a psychiatric day clinic sample: results and requirements for systematic diagnostic - Hader, Saskia; Kratz, Oliver; Eichler, Anna; Moll, Gunther; Irlbauer-Müller, Viktoria (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2021)
Sleep behavior and problems in children and adolescents of a psychiatric day clinic sample: results and requirements for systematic diagnostic Abstract. Sleep disorders are common in adults as well as children and adolescents. Children and adolescents in psychiatric treatment (CAP) are especially affected by sleep problems. Cognitive behavioral therapy represents the first-line treatment, preceded by a standardized procedure for sleep diagnostics. To date, no study has investigated sleep behavior in CAP day clinics in Germany. In this study, N = 46 children/adolescents receiving CAP treatment in a day clinic completed a sleep diary (7 days) and a sleep anamnesis scheme with the help of their parents, and their sleep behavior was assessed by a clinician. Furthermore, a parent- and a self-report questionnaire plus a clinical assessment of the mental disorders in the children/adolescents were collected. 52 % of the children/ adolescents exhibited sleep disorders or sleep abnormalities (= sleep disorder symptoms in the context of comorbid disorders), in particular problems falling asleep or to falling asleep and sleeping through the night (26 %). In addition, 33 % reported having nightmares. Their sleep behavior correlated significantly with their external behavior problems (r = .38 .61, p = .02-.04); their sex (female: p = .01-<= .001, |d| = 1.57-2.50) and their age (older: p = .05, |d| = .78) also significantly influenced sleep behavior. Particularly external behavior problems were associated with sleep problems in this day-care population. In summary, a multi-method-multi-informant procedure should be established for the systematic diagnostics of sleep abnormalities, together with individualized cognitive-behavioral therapy of sleep problems, especially in patients with external behavior problems.
CRIS-Team WoS Importer:2021-09-10

Stress system dysregulation in pediatric generalized anxiety disorder associated with comorbid depression - Funke, R.; Eichler, Anna; Distler, Jörg; Golub, Yulia; Kratz, Oliver; Moll, Gunther (Stress and Health, 2016)
Because chronic stress is an important risk factor for anxiety states and depressive disorders, we studied hypothalamus-pituitary-adrenal (HPA) axis and sympathetic system activity via changes in cortisol and alpha amylase activity levels in pediatric generalized anxiety disorder (GAD) patients (n = 26) with comorbid depression and a healthy comparison group (n = 26). Morning plasma cortisol and diurnal profiles of salivary cortisol and salivary alpha amylase (sAA) activity were assessed, also reactivity of HPA-axis, sAA activity, and heart rate following a psychosocial stressor (Trier Social Stress Test for children). GAD patients with comorbid depression showed increased morning plasma and salivary cortisol levels, ameliorating throughout in-patient treatment, and higher sAA activity in their diurnal profile. Both HPA and sympathetic activity positively correlated with the severity of anxiety and depression. We also demonstrated a blunted HPA and sympathetic response to acute stress in patients. This pattern of neuroendocrine and sympathetic changes seems to be distinct from the one previously reported in pediatric patients with only social anxiety or depressive disorders. We propose morning plasma and saliva cortisol levels as potential physiological indicators for supporting the evaluation of symptoms' severity and treatment progress in children with GAD and comorbid depressive disorder.
EVALuna2:23891

The association between prenatal alcohol consumption and preschool child stress system disturbance - Grimm, Jennifer; Stemmler, Mark; Golub, Yulia; Schwenke, Eva; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Developmental Psychobiology, 2021)
Background: Drinking alcohol during pregnancy is considered a risk factor for child development; however, child biomarkers of prenatal alcohol exposure have been rarely studied. We examined whether a meconium alcohol metabolite (ethyl glucuronide, EtG) was associated with child cortisol concentrations at primary school age. Methods: For 137 children, prenatal alcohol exposure was operationalized by the meconium biomarker EtG and by maternal self-reports during pregnancy. Two EtG cut-offs (EtG ≥10 ng/g and EtG ≥112 ng/g) were applied. Cortisol concentrations were measured in saliva and hair samples. Results: Children with EtG ≥10 ng/g showed significantly reduced hair cortisol concentrations (HCCs) (p =.050, (Formula presented.) = 0.042). For children with EtG ≥112 ng/g, the cortisol awakening response (CAR) was significantly decreased (p =.025, (Formula presented.) = 0.070). These effects were also present in correlational analyses with continuous EtG data, speaking for partly dose-dependent effects. Especially, within the EtG ≥112 ng/g group, the basal (CAR: rp = −.642, p =.120) and cumulative (HCC: rp = −.660, p =.107) cortisol parameters were associated with child emotional symptoms at medium effect size. Conclusions: The present study showed both the biological association of intrauterine alcohol exposure with the cortisol stress system, partly dose-dependent, and the functional association with emotional and behavioral symptoms.
CRIS-Team Scopus Importer:2020-10-16
Keywords: alcohol; biomarker; child; cortisol stress system; ethyl glucuronide; hypothalamus-pituitary-adrenal axis; intrauterine alcohol exposure; meconium; pregnancy

The Benefit of a Retrospective Pregnancy Anamnesis in Child and Adolescent Psychiatry: The Reliability of Maternal Self-Report during Childhood Development - Mestermann, Stefan; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Children, 2023)
Pregnancy anamnesis is a crucial part of child and adolescent psychiatry diagnostics. In previous works, the reliability of retrospective maternal self-report on perinatal characteristics was heterogeneous. This prospective longitudinal study aimed to evaluate women’s recall of prenatal events in a within-subject design. A sample of 241 women gave a self-report on prenatal alcohol, smoking, partnership quality, pregnancy satisfaction, and obstetric complications during the 3rd trimester (t0), childhood (t1, 6–10 y), and adolescence (t2, 12–14 y). The intra-individual agreement was examined. The t0–t1–(t2) agreement was poor to substantial; this was highest for smoking and worst for obstetric complications, followed by alcohol (Fleiss’ κ = 0.719 to −0.051). There were significant t0–t1–(t2) differences for all pregnancy variables (p < 0.017), except for 3rd trimester satisfaction (p = 0.256). For alcohol (t0 25.8%, t1 17.4%, t2 41.0%) and smoking (t0 11.9%, t1 16.4%, t2 22.6%), the highest self-reported rates were found during adolescence. During childhood, fewer obstetric complications (t0 84.9%, t1 42.2%) and worse partnerships were reported (t0 M = 8.86, t1 M = 7.89). Thought to be due to social stigmata and memory effects, pregnancy self-reports cannot be precisely reproduced. Creating a respectful and trusting atmosphere is essential for mothers to give honest self-reports that are in the best interest of their children.
CRIS-Team Scopus Importer:2023-06-30
Keywords: alcohol; partnership; pregnancy; pregnancy satisfaction; prenatal; retrospective; risk perceptions; self-report; smoking

The Father’s Part: A Pilot Evaluation of a Father-Centered Family Intervention Group in Child and Adolescent Psychiatry - Mestermann, Stefan; Kleinöder, Jonas; Arndt, Marie; Krämer, Josef; Eichler, Anna; Kratz, Oliver (Behavioral Sciences, 2024)
Changes in parental roles have renewed the focus on a father’s involvement in an offspring’s psychological development. However, fathers are still under-represented in family research. There are only a few structured father-centered intervention programs in child and adolescent psychiatry. In a German population sample, a pilot father-centered family intervention program with n = 16 participants, conducted in person (n = 8) and online (n = 8), in a child and adolescent psychiatry inpatient/day clinic setting was evaluated by comparing paternal stress, PSE, and child-rated paternal competence in a pre–post design. Participating fathers showed significant decreases in child-related parenting stress (presence: p = 0.042, online: p = 0.047) and significant increases in PSE (p = 0.006/0.012). Parent-related stress and child-rated paternal competence were unaffected (p = 0.108/0.171; p = 0.167/0.101), while small-to-medium effect size measures pointed in the direction of our hypothesis (d = 0.48/0.36; d = 0.37/0.50). Participant satisfaction was higher in person than online (p = 0.008). As social and biological fathers have important influences on child and adolescent well-being and development, they should be included more frequently in prevention and intervention programs. Fathers seem to benefit from gender-specific intervention programs with regard to stress reduction, as well as experiencing competence- and PSE-increasing effects.
CRIS-Team Scopus Importer:2024-03-08
Keywords: child development; parent-centered interventions; parental behavior; parenting stress; parent–child-relation

The Father’s Part: Influences of Paternal Psychopathology and Parenting Behavior on Child and Adolescent Well-Being - Mestermann, Stefan; Arndt, Marie; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Healthcare, 2023)
Family influences on child quality of life (QoL) are increasingly understood. Parenting behavior and parent individual psychopathology are among the established predictors of offspring mental health. However, literature often addresses these factors as ‘parental’, lacking further gender-specific differentiation while predominantly studying maternal aspects. Social and biological fathers are still underrepresented in family research. The aim of this study was to analyze paternal contributions to child well-being. A total of 197 father/mother-dyads gave a standardized self-report on parenting behavior and their own psychopathology at child primary school age (t1; 6–10 y). Ratings were compared mutually and associated with child self-rated QoL at t1 and adolescence (t2; 12–14 y). Fathers and mothers differed in psychopathology and most parenting behavior dimensions (positive parenting, involvement, responsible parenting, poor monitoring, and corporal punishment). Father psychopathology made a relevant predictive contribution to girls’ QoL at t2. Boys’ t1 QoL was significantly influenced by maternal parenting factors (positivity and corporal punishment). Compared to mothers, fathers are faced with different individual stressors; paternal parenting behavior is different, while fathers’ influences are significant, particularly for daughters. Father-addressed pre- and intervention programs in child psychotherapeutic treatment are of high relevance.
CRIS-Team Scopus Importer:2023-08-25
Keywords: child development; father; parent-child-relations; parental influence; parenting; parenting behavior; resilience

The impact of early surgical ventricular septal defect repair on parenting behavior and mother-child relationship: a prospective longitudinal study - Hemetsberger, Jonas; Mestermann, Stefan; Nicol, Hannah; Purbojo, Ariawan; Cesnjevar, Robert A.; Kratz, Oliver; Eichler, Anna; Gerlach, Jennifer (Frontiers in Pediatrics, 2024)
Introduction: Many studies have investigated the impact of congenital heart defects (CHD) on child development. However, because CHD not only affects the child and his or her development but, also the entire family, family functioning after pediatric cardiac surgery is of increasing research interest. This prospective childhood-adolescence case-control study aimed to examine differences and changes in parenting behavior and mother-child relationship quality after early surgical repair of an isolated ventricular septum defect (VSD) compared to non-affected controls. Patients and methods: 39 affected children (M = 7.3 years) with surgically repaired VSD and their mothers were compared with a matched, non-affected control group of 39 mother-child-dyads (M = 7.3 years) during primary school age (t1). At child early adolescence, 24 affected children (M = 12.4 years) and 24 children of the control group (M = 13.2 years) were examined again (t2). Parenting behavior characteristics (t1: mother report; t2: mother- and child report) and mother-child relationship quality (t2: child report) were measured by standardized questionnaires. Results: The mother-rated parenting behavior dimensions Involvement (p <.001, η2p =.37), Parental Monitoring (p =.014, η2p =.17) and Corporal Punishment (p <.001, η2p =.57) significantly decreased from t1 to t2 in both cohorts. Responsible Parenting Behavior tended to decrease from t1 to t2 in the control group, while remaining stable in the VSD-group (p =.088, η2p =.09). Independent of the group, higher mother-child relationship quality was associated with more Positive Parenting Behavior (p <.001, η2p =.34), more Involvement (p =.003, η2p =.22) and fewer Inconsistency (p <.001, η2p =.31) in the child-rating; and more Positive Parenting Behavior in the mother-rating (p =.039, η2p =.10). Conclusion: VSD affected mother-child-dyads were mostly comparable in their parenting behavior characteristics and mother-child relationship quality to non-affected controls. The absence of a decrease in maternal Responsible Parenting Behavior in the VSD group may indicate challenges during the developmental task of autonomy in adolescence. Nevertheless, adaptive family functioning after early pediatric surgical VSD repair seems possible.
CRIS-Team Scopus Importer:2024-11-22
Keywords: congenital heart disease; longitudinal study; mother; mother-child relationship; parenting behavior; pediatric cardiac surgery; ventricular septal defect

The influence of prenatal risks on attachment, emotion regulation and emotional and behavioral problems in middle childhood: A prospective longitudinal study - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)